Bandwidth and gain enhancement of RMPA using ‘c’ shaped metamaterial at THz - Dawar, Parul; De, Asok (International Journal of Scientific World, 2015)
This paper elucidates antenna parameter optimization using C shaped metamaterial embedded in antenna substrate at high frequency (THz). Ansoft HFSS version 13 has been used to design and analyse the RMPA (Rectangular Microstrip Patch Antenna ) with design frequency 2.75 THz and operating range of 2.15 THzÂ to 3.35 THz having FR4 (Îµr = 4.4) as substrate material . Nicolson Ross Wier (NRW) method has been used to retrieve the material parameters from transmission and reflection coefficient. . Results were compared with MATLAB programming based on CAD formulas using equivalent circuit analysis of patch antenna. Finally, antenna parameters such as gain, bandwidth, and radiation pattern are investigated and presented in tables and response-graphs. The unique shape proposed in this paper, gives remarkable enhancement in bandwidth and antenna gain.